Isolation and molecular detection of Pasteurella multocida Type A from naturally infected chickens, and their histopathological evaluation in artificially infected chickens in Bangladesh (Journal of Advanced Veterinary and Animal Research, 2015)
Pasteurella multocida type A is the etiologic agent of fowl cholera, a highly contagious and fatal disease of chickens. The present research work was performed for the isolation, identification and molecular detection of P. multocida Type A from chickens. Liver, heart and spleen of suspected dead chicken (n=35) were collected from Gazipur and Pabna districts in Bangladesh. The targeted bacteria from the samples were isolated, identified and characterized based on their morphology, staining, cultural, biochemical characters, pathogenicity test, histopathological study and Polymerase Chain Reaction (PCR). The P. multocida organism was isolated from 11.42% (n=4/35) samples. The organisms were gram negative, non-spore forming rod, non-motile, occurring singly or pairs in Gram staining, whereas in Leishmans stain, bipolar shaped organisms were observed. All the isolates were found positive for oxidase and catalase tests, produced indole, and fermented glucose, mannitol and sucrose. Necrotic foci in liver and congestion with hemorrhages in heart were found on necropsy. After pathogenicity test, the pathological changes were reconfirmed by histopathology depicting congestion, hemorrhage and lymphocyte infiltration in heart, liver and spleen tissues. In type specific PCR reaction, the organisms were confirmed as P. multocida Type A. In conclusion, P. multocida type A is prevalent among poultry in the studied regions; thus, care must be taken to control of the disease. http://dx.doi.org/10.5455/javar.2015.b104